Moon light and the activity patterns of Bairdâ€™s tapir in the Calakmul region, Southern México - Sanchez-Pinzon, Khiavett; Reyna-Hurtado, Rafael; Meyer, Ninon F. V. (THERYA, 2019)
The Baird’s tapir (Tapirella bairdii) is an endangered species throughout its distribution area, however many aspects of its biology and ecology have been poorly studied, due to its evasive behavior and low densities. The goal of this study was to evaluate the activity patterns of T. bairdii, a large ungulate species from the Neotropics, in relation to moon phases in two sites with different degree of human perturbation: the Calakmul Biosphere Reserve (CBR) and the Nuevo Becal (NB) community. We monitored twenty waterbodies in each site for 18 months using camera traps. The photographic capture rate (CR) and the corresponding moon phases for both sites were recorded. The CR of T. bairdii was 0.054 in NB and 0.029 in CBR. T. bairdii was more active at night and dawn-twilight periods. In general, T. bairdii showed major activity during the dark moon phases but the differences with the light phases were not statistically significant. However, we found a trend of tapirs to be more active in dark nights and in the darkest hours in NB than CBR. The apparent preferences for dark nights in NB could be caused by the perturbation caused by human activities at site, which may have influenced the behavior of the tapir that avoid moving out in periods of abundant light in disturbed sites. More research is needed to confirm this finding.